Body composition of women's ice hockey players: Comparison of estimates using skinfolds and iDXA - Gilenstam, K.; Geithner, C. A. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to compare percent fat (% fat) estimates from anthropometric equations using skinfolds (SKF) in women's ice hockey players with estimates obtained from Lunar iDXA. Data were collected on 19 elite female Swedish hockey players (mean age ± SD = 18.4 ± 2.4 years). Four SKF (triceps, abdominal, suprailiac, and thigh) were measured within 2 hours of iDXA assessments. The % fat estimates from iDXA and 4 anthropometric equations were compared using paired t tests, and a 1-way analysis of variance was used to compare % fat estimates from the anthropometric equations. Bland-Altman analyses were used to assess agreement between % fat estimates from SKF and iDXA. The significance level was set a priori at p = 0.05. The % fat estimates from anthropometric equations were significantly lower than those from iDXA (mean ± SD: 26.85 ± 4.93%, p = 0.000). Bland-Altman analyses indicated mean differences of -7.96 to -10.13 percentage points between anthropometric equations and iDXA. Estimates of % fat from anthropometric equations (range: 16.72-18.89%) were within the range reported in earlier studies using the sum of 7 SKF. Thus, SKF offer a reasonable alternative to iDXA for this population but result in underestimates of % fat relative to iDXA. Strength and conditioning coaches should use the same body composition assessment method consistently, and interpret the results with caution, as they are estimates and not true values.